Systemic treatment of alopecia areata - Łuczak, Magdalena; Łuczak, Tomasz; Cieścińska, Czanita; Czajkowski, Rafał (Dermatology Review/Przegląd Dermatologiczny, 2013)
Alopecia areata is a recurrent, non scarring type of hair loss. Etiologic factors have not been fully explored. The incidence of the disease is estimated to be 1-2% of the general population. Therapeutic management can be divided into local and general treatment, phototherapy and psychological support. The choice of method depends on the type of alopecia areata, the general condition of the patient and the experience of the leading treatment center. The aim of the present study was to review and organize current knowledge and research on the general treatment of alopecia areata.